2022
DOI: 10.3390/su14031918
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of RC Beam–Column Joints Strengthened with Modified Reinforcement Techniques

Abstract: Using a significant number of transverse hoops in the joint’s core is one recognized way for achieving the requirements of strength, stiffness, and ductility under dynamic loading in a column joint. The shear capacity of a joint is influenced by the concrete’s compressive strength, the anchoring of longitudinal beam reinforcement, the number of stirrups in the joint, and the junction’s aspect ratio. Seismic motion on the beam may produce shear capacity and bond breaking in the joint, causing the joint to fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Figure 12 shows the dynamic modulus of elasticity of the control mix and concrete containing marble dust and foundry sand subjected to increased temperatures of 200 °C, 400 °C, 600 °C, 800 °C, and 1000 °C. Elevated temperature causes considerable damage to the cement matrix, according to the dynamic modulus of elasticity [ 17 , 28 , 35 , 39 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. In all cases of concrete exposed to extreme temperatures ranging from 200 °C to 1000 °C, the dynamic modulus of elasticity was shown to be reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 12 shows the dynamic modulus of elasticity of the control mix and concrete containing marble dust and foundry sand subjected to increased temperatures of 200 °C, 400 °C, 600 °C, 800 °C, and 1000 °C. Elevated temperature causes considerable damage to the cement matrix, according to the dynamic modulus of elasticity [ 17 , 28 , 35 , 39 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. In all cases of concrete exposed to extreme temperatures ranging from 200 °C to 1000 °C, the dynamic modulus of elasticity was shown to be reduced.…”
Section: Resultsmentioning
confidence: 99%
“…However, at higher temperatures (1000 °C), it increased by approximately three times, indicating fast degradation in all mixtures. This is owing to the development of large voids in both mixtures due to the dehydration of the C-S-H gel [ 17 , 28 , 35 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. Due to the differences in water absorption of the two distinct materials, concrete mixes comprising marble dust and foundry sand absorb less water than control mixes.…”
Section: Resultsmentioning
confidence: 99%
“…From the permeability result, it is also found that coefficient of permeability with 2 percent soap solution is very much less in comparison with 0 percent soap solution. From the observation of SEM images, it can be said that soap solution helps in filling the voids of concrete which ultimately helps in reduction in permeability [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. EDX analyses of concrete with 0% (M1) and 2 % (M6) soap solution are shown in Figure 9 and Figure 10 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Various crack depth effects were taken and compared with the beam without crack. It was discovered that the lowest frequency response of a beam without deformation was significantly greater than the lowest frequency obtained from the beam with a crack [13].…”
Section: Literature Reviewmentioning
confidence: 97%